Circulating ghrelin crosses the blood-cerebrospinal fluid barrier via growth hormone secretagogue receptor dependent and independent mechanisms. (1st December 2021) - Uriarte, Maia; De Francesco, Pablo N.; Fernández, Gimena; Castrogiovanni, Daniel; D'Arcangelo, Micaela; Imbernon, Mónica; Cantel, Sonia; Denoyelle, Severine; Fehrentz, Jean-Alain; Praetorius, Jeppe; Prevot, Vincent; Perello, Mario
Abstract: Ghrelin is a peptide hormone mainly secreted from gastrointestinal tract that acts via the growth hormone secretagogue receptor (GHSR), which is highly expressed in the brain. Strikingly, the accessibility of ghrelin to the brain seems to be limited and restricted to few brain areas. Previous studies in mice have shown that ghrelin can access the brain via the blood-cerebrospinal fluid (CSF) barrier, an interface constituted by the choroid plexus and the hypothalamic tanycytes. Here, we performed a variety of in vivo and in vitro studies to test the hypothesis that the transport of ghrelin across the blood-CSF barrier occurs in a GHSR-dependent manner. In vivo, we found that the uptake of systemically administered fluorescent ghrelin in the choroid plexus epithelial (CPE) cells and in hypothalamic tanycytes depends on the presence of GHSR. Also, we detected lower levels of CSF ghrelin after a systemic ghrelin injection in GHSR-deficient mice, as compared to WT mice. In vitro, the internalization of fluorescent ghrelin was reduced in explants of choroid plexus from GHSR-deficient mice, and unaffected in primary cultures of hypothalamic tanycytes derived from GHSR-deficient mice. Finally, we found that the GHSR mRNA is detected in a pool of CPE cells, but is nearly undetectable in hypothalamic tanycytes with current approaches. Thus, our results suggest that circulating ghrelin crosses the blood-CSF barrier mainly by a mechanism that involves the GHSR, and also possibly via a GHSR-independent mechanism. Highlights: Choroid plexus cells internalize less Fr-ghrelin in GHSR-deficient mice. Hypothalamic tanycytes internalize Fr-ghrelin in a GHSR-independent manner. Systemically-injected ghrelin shows lower transport to CSF in mice lacking GHSR. Ghsr mRNA is detected in choroid plexus cells, but undetectable in tanycytes.